2008
DOI: 10.1111/j.1444-2906.2008.01589.x
|View full text |Cite
|
Sign up to set email alerts
|

Underwater sound detection by cephalopod statocyst

Abstract: The cephalopod receptor of particle motion was identified. In a previous study, it was suggested that statocysts served this function, but there was no direct supporting evidence, and epidermal hair cells had not been conclusively ruled out. Experiments on Octopus ocellatus were conducted using respiratory activity as an indicator of sound perception. Intact animals clearly responded to 141-Hz particle motion at particle accelerations below 1.3 ¥ 10 -3 m/s 2 , and the mean perception threshold at this frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 23 publications
1
42
0
1
Order By: Relevance
“…The overall frequency range and upper limit that generated responses was somewhat greater than in previous acceleration-based cephalopod sound detection studies (Packard et al, 1990;Kaifu et al, 2008;Mooney et al, 2010), but the results were similar to those of many fish without auditory specializations (Popper and Fay, 2011). This reinforces the notion that cephalopods, like many fish, have an accelerometer-like 'auditory' system that detects the particle motion component of sound stimuli.…”
Section: Discussion Acoustic Frequency Range and Sensitivitysupporting
confidence: 56%
See 2 more Smart Citations
“…The overall frequency range and upper limit that generated responses was somewhat greater than in previous acceleration-based cephalopod sound detection studies (Packard et al, 1990;Kaifu et al, 2008;Mooney et al, 2010), but the results were similar to those of many fish without auditory specializations (Popper and Fay, 2011). This reinforces the notion that cephalopods, like many fish, have an accelerometer-like 'auditory' system that detects the particle motion component of sound stimuli.…”
Section: Discussion Acoustic Frequency Range and Sensitivitysupporting
confidence: 56%
“…The differences between the physiology and behavior results could reflect that the evoked potential methods are not as sensitive as the animal's auditory system and these behavioral metrics. Or there could be taxonomybased differences as this study used cuttlefish, while Kaifu et al (Kaifu et al, 2007;Kaifu et al, 2008) and Mooney et al (Mooney et al, 2010;Mooney et al, 2012) used octopus and squid species. Yet, Packard et al (Packard et al, 1990) used classical conditioning to address S. officinalis sound detection, and response thresholds were still two orders of magnitude higher than here.…”
Section: Discussion Acoustic Frequency Range and Sensitivitymentioning
confidence: 97%
See 1 more Smart Citation
“…Behavioral conditioning experiments later confirmed that squid (Loligo vulgaris), octopus (Octopus vulgaris) and S. officinalis can detect acceleration stimuli from 1-100 Hz, presumably by using the statocyst organ as an accelerometer detecting the body movements of the squid in the sound field (Packard et al 1990). This and a follow-up study (Kaifu et al 2008) showed that cephalopods can detect the low-frequency particle motion component of a sound field, but the question whether cephalopods are also sensitive to higher-frequencies and sound pressures still remained. Recent laboratory experiments have demonstrated that squid do not exhibit anti-predator responses in the presence of odontocete echolocation clicks (Wilson et al 2007) indicating that they cannot detect the ultrasonic pressure component of a sound field.…”
Section: The Sensitivity Of Squid To Acoustic Stimulimentioning
confidence: 99%
“…The statocyst is analogous to the fish otolith system (Fay, 1974) and, to some extent, may share functions of the inner ear hair cells of higher vertebrates (Yost, 1994). Because squid are now considered to respond to some acoustic components, there is concern that increases in ocean noise may damage statocyst hair cells and impact their hearing (Packard et al, 1990;Budelmann et al, 1992;Kaifu et al, 2008;Hu et al, 2009;André et al, 2011;Mooney et al, 2012;Solé et al, 2013). Additionally, squid have been a model species in physiology and neuroscience since the classic experiments by Hodgkin and Huxley on the nature of the action potential Huxley, 1945, 1952), and their use is growing in other areas such as the study of camouflage and animal-bacterial symbioses (Hanlon, 2007;Lee et al, 2009).…”
Section: Introductionmentioning
confidence: 99%